SOME FACTORS AFFECTING TDS AND PH VALUES IN GROUNDWATER OF THE BEIHAI COASTAL AREA IN SOUTHERN GUANGXI, CHINA - Xun Zh.; Hua Zh.; Liang Zh.; Ye Sh.; Xia Ya.; Rui L.; Li Zh. (My University, 2007)
Groundwater of low total dissolved solids (TDS) of 10 mg/L and low pH ranging commonly from 4.0 to 7.0 occurs in the unconsolidated unconfined and confined aquifers in the coastal plain near Beihai, Guangxi, China. Minerals in the unconsolidated sediment of Quaternary are predominated by quartz (more than 50%) with small amount of clay minerals, such as kaolinite, illite and chlorite. SiO2 accounts for most (more than 70%) of the chemical compositions of the sediments. The sediments contain low concentrations of soluble constituents (below 300 μg/g) and are predominated by SO4. Abundant recharge from low-TDS precipitation and a long time’s dissolution of the unconsolidated sediments containing small amount of soluble compositions lead to low TDS of the groundwater in the area.
Keywords: COASTAL AQUIFER; RAINWATER; ACIDIC GROUNDWATER; TDS; PH; SOLUBLE ION; Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная